THE CONVERSION RATE IN LAPORASCOPIC CHOLECYSTECTOMY IN PATIENTS COMPLAINING OF ACUTE AND CHRONIC CHOLECYSTITIS (Iraqi Journal of Medical Sciences, 2016)
Background: Laparoscopic cholecystectomy is the gold standard in the treatment of cholelithiasis, but there are still some patients requiring conversion to open cholecystectomy for several factors.Objective:To estimate the conversion rate and evaluate preoperative risk factors for conversion from laparoscopic to open cholecystectomy.Methods: 140 laparoscopic cholecystectomies were carried out from January 2008 to January 2011 at Al-Kindy Teaching Hospital. Preoperative clinical, laboratory and radiographic parameters for these patients assessed and analyzed prospectively.Results:Conversion to open cholecystectomy was needed in 30 patients (21.4%). Multivariate analysis identified male sex, with positive Murphy's sign, gall bladder wall thickness > 3 mm, a history of acute cholecystitis and time from the onset of symptoms till the time of surgery > 3 days as independent predictors of conversion rate to open cholecystectomy.Conclusion:The identification of certain risk factors for conversion from laporascopic to open cholecystectomy preoperatively such as male gender, age more than 40 years, onset of symptoms, gallbladder wall thickness can help the surgeon to plan and counsel the patients about the conversion rate.Keywords:Acute cholecystitis, laporascopic cholecystectomy, open cholecystectomy
Keywords: Acute cholecystitis; laporascopic cholecystectomy; open cholecystectomy